2020
DOI: 10.1109/access.2020.3019978
|View full text |Cite
|
Sign up to set email alerts
|

Hands-Free Accessible Digital Musical Instruments: Conceptual Framework, Challenges, and Perspectives

Abstract: Exponential increases of available computational resources, miniaturization, and sensors, are enabling the development of digital musical instruments that use non-conventional interaction paradigms and interfaces. This scenario opens up new opportunities and challenges in the creation of accessible instruments to include persons with disabilities into music practice. This work focuses in particular on instruments dedicated to people who can not use limbs, for whom the only means for musical expression are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 105 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, the field of accessible digital musical instruments (ADMI), dedicated to instruments designed for people with disabilities, is growing rapidly, with the recognition that adaptations of existing digital musical instruments can promote inclusive music making [14][15][16]. ADMI offer opportunities to engage with a wider range of sounds than acoustic instruments can provide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the field of accessible digital musical instruments (ADMI), dedicated to instruments designed for people with disabilities, is growing rapidly, with the recognition that adaptations of existing digital musical instruments can promote inclusive music making [14][15][16]. ADMI offer opportunities to engage with a wider range of sounds than acoustic instruments can provide.…”
Section: Resultsmentioning
confidence: 99%
“…ADMI offer opportunities to engage with a wider range of sounds than acoustic instruments can provide. Some ADMI use eye-tracking through head movements [14][15][16], releasing the user from interfaces dependence such as keyboard and mouse to interact with sounds. Furthermore, some authors have implemented a simple study method, based on a set of exercises, to aid the use of ADMI [16], thus providing greater opportunities for exploration, improvisation, empowerment and fluidity in music production for users with or without SN [14][15][16][17][18][19]22].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, our study found that 3 of all 20 instruments were designed with the intention to be controlled in multiple different ways. However, having these various methods of input makes a single instrument highly more useful to a wider range of users -yet these multi-input devices are largely unexplored [8]. Many of the organizations studied within this survey, such as OHMI Trust and Drake Music, frequently work alongside engineering educators and students to develop their prototypes and encourage collaboration between engineers and disabled musicians to create effective, accessible music technology.…”
Section: Insights For Engineering Educatorsmentioning
confidence: 99%
“…Similarly, there is space for exploring different mappings strategies and more complex mapping cardinalities." [8]. Though prior research has proven the presence of design and study of accessible music instruments, further study must be done to determine how prototypes and past concepts have been effectively used by physically disabled musicians, whether intended for that audience or otherwise proven useful to that audience.…”
mentioning
confidence: 99%